Tobacco and alcohol policies and measures. Closing remarks from the 2nd World Calisia Conference on Family Health - Aarø, Leif; Zatoński, Mateusz; Janik-Koncewicz, Kinga; Zatoński, Witold (Journal of Health Inequalities, 2021)
During the 2nd World Calisia Conference on Family Health in Poland, a number of presentations focussed on smoking and use of alcohol. In this text, some of the presentations on smoking are discussed within the “Diffusion of innovations” theoretical framework. A selection of the presentations on alcohol use are referred to and changes in alcohol use are examined in the context of national alcohol control programmes. Finally, new evidence of inequalities between and within countries are examined. Comprehensive action to reduce burden of disease and health inequalities caused by tobacco and alcohol as documented during this conference is urgently needed.